Preeclampsia and its relationship to pathological brain aging - Testo, Abigail A.; McBride, Carole; Bernstein, Ira M.; Dumas, Julie A. (Frontiers in Physiology, 2022)
The development of preeclampsia during pregnancy may have long-term effects on brain aging in women. Associations between preeclampsia and vascular dementia have been established, however the connection between preeclampsia and Alzheimer’s disease has not been as thoroughly explored. Both preeclampsia and Alzheimer’s disease have been associated with misfolded amyloid beta proteins and inflammation; due to these similarities, in this minireview, we examined the potential links between a history of preeclampsia and the development of dementia. We also discussed how hypertensive disorders of pregnancy may relate to both normal brain aging and dementia to highlight the need for additional research regarding the long-term cognitive effects of preeclampsia on the brain.